Optimum Condition for Peroxidase Activity in Crude Extract of Loranthus europaeus - Shaema Saadon Fadel (Journal of Global Pharma Technology, 2016)
In this study peroxidase was extracted from fruit part of Loranthus europaeus then peroxidase activity was detected and optimized. Optimum conditions for the activity of crude peroxidase were studied. Results showed maximum activity of peroxidase was achieved 0.5125U/ml when the enzyme was incubated with 1mM of 4-aminoantipyrine at 40 oC for 10 minutes in the presence of 0.2M of potassium phosphate buffer solution at PH7.Keywords: Loranthus europaeus, Peroxidase, enzyme activity.